2015
DOI: 10.1128/jvi.00587-15
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cholesterol 25-Hydroxylase as a Novel Host Restriction Factor and a Part of the Primary Innate Immune Responses against Hepatitis C Virus Infection

Abstract: Hepatitis C virus (HCV), a single-stranded positive-sense RNA virus of the Flaviviridae family, causes chronic liver diseases, including hepatitis, cirrhosis, and cancer. HCV infection is critically dependent on host lipid metabolism, which contributes to all stages of the viral life cycle, including virus entry, replication, assembly, and release. 25-Hydroxycholesterol (25HC) plays a critical role in regulating lipid metabolism, modulating immune responses, and suppressing viral pathogens. In this study, we s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 53 publications
7
50
0
Order By: Relevance
“…CH25H is an interferon-stimulated gene, and its expression is upregulated during infection with hepatitis C and influenza viruses (16, 29). How LASV infection upregulates CH25H is unknown, especially since LASV-infected human cells produce undetectable or very low levels of type-I IFN (30, 31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CH25H is an interferon-stimulated gene, and its expression is upregulated during infection with hepatitis C and influenza viruses (16, 29). How LASV infection upregulates CH25H is unknown, especially since LASV-infected human cells produce undetectable or very low levels of type-I IFN (30, 31).…”
Section: Discussionmentioning
confidence: 99%
“…The antiviral function of 25HC involves multiple mechanisms, including blocking fusion of the viral envelope with host membranes (14), inhibiting viral replication (14, 15), and inhibiting the formation of viral replication complexes on intracellular membranes (17). 25HC was also reported to inhibit a postentry step of viral infection by repressing the activation of SREBP (16), a transcription factor required for lipid and cholesterol biosynthesis. More recently, 25HC has also been shown to block the replication of nonenveloped viruses (18).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also revealed more detail regarding the regulation of CH25H. Mboko et al (93) showed that CH25H expression in mice is, at least partly, dependent on IRF1 and Xiang et al (94) demonstrated an IFN-independent induction of CH25H in hepatocytes in response to viral infection (93, 94). In this regard, evidence to-date suggests that CH25H gene expression is regulated in a cell-specific manner and it cannot be considered a prototypic ISG.…”
Section: Broad Antiviral Functionality Of 25-hcmentioning
confidence: 99%
“…42,81 Notably, a number of studies have identified anti-viral activity of CH25H/25-HC against HCV potentially involving multiple mechanisms. 43,69,78,79,8587 Finally, an exciting study has been published recently examining the non-coding transcriptome in HCV-infected cells in the presence and absence of 25-HC treatment, demonstrating that 25-HC alters the miR environment of these cells. miR-185 and miR-130b were shown to be induced by 25-HC treatment in infected cells and to inhibit HCV through a mechanism involving regulation of hepatic lipid metabolism and virus-induced lipid microenvironments (miR-185 and miR-130b) and an effect on IFNs (miR-130b).…”
Section: Ifns and Sterol Metabolismmentioning
confidence: 99%
“…31 Similarly, regulation of inflammasome components by SREBPs has been suggested to be an artefact of back-crossing deficits in in-bred mouse strains. 95 At least one report has challenged IFN sensitivity of CH25H in humans 87 and, in particular, many aspects of CH25H and 25-HC expression and regulation are not understood in humans, where protein expression of CH25H is reported to be low. 85 With these concerns in mind, acknowledgment must be made of studies that include a focused effort to realize applicability of findings across experimental models and consider translational impact.…”
Section: Concluding Remarks: Outlookmentioning
confidence: 99%